The Effect of Artificial Intelligence (AI) Chat GPT and Hard Work Character on College Students' Critical Thinking Skill - Ramadhanti, Safira Rizki; Patmisari, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to determine the effect of Artificial Intelligence (AI) Chat GPT and hard work character on students' critical thinking skills. Methodology: This study uses a quantitative method with a correlational design. The popu-lation in this study was 5,582,774 students who live in Java. The sample tak-en in this study was 270 students. Data collection techniques involve distrib-uting questionnaires to students who fit the criteria. This study uses prerequi-site test data analysis techniques, namely the normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing is done using the T test and F test. Results: The results showed a positive relationship between the use of Chat GPT and students' critical thinking skills. There is a positive influence between the use of Chat GPT on critical thinking skills characterized by 207 or 76.7% of stu-dents have high knowledge, skills in using, and frequency of using Chat GPT. There is also a positive relationship between the character of hard work and students' critical thinking skills, which is characterized by 208 or 77% of students having a hard work character during their college life. Students who have critical thinking skills or high level thinking are 241 or 89.3% of students. Applications/Originality/Value: This research can be a reference material for developing more effective learning methods in the digital era. The renewal of this research with previ-ous studies is because it combines two variables simultaneously, namely the use of Chat GPT and the character of hard work on students' critical thinking skills.